The Drama of Shalahuddin al-Ayyubi and Natana al-Hakim | مسرحية صلاح الدين الأيوبي وناتان اليهودي دراسة نقدية - Abdul Muhsin Al-Qaysi (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2008)
Drama can be for politics, social, or for religiousinterest, as can be seen in the case of Natana a/Hakimand Shalahuddin al-Ayyubi. Through literaturecritic approach, the writer proves that Natana a/Hakimand Shalahuddin al-Ayyubi drama is part ofthe Jewish-Freemasonry projects. From literaturecritic point of view the writer also presents theshortage and constructive aspects of the drama.